2023
DOI: 10.3928/01477447-20230207-03
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Flexible Rods for Correction of Severe Pediatric Spinal Deformity

Abstract: Surgical correction of large, rigid scoliotic and kyphotic curves carries an increased risk of perioperative complications, such as neurological injury and excessive blood loss, compared with correction of less severe curves. Titanium temporary flexible rods (TFRs), designed for pediatric long bone fracture fixation, may be helpful as adjuncts to achieve gradual, stepwise intraoperative correction of severe pediatric spinal deformities. A retrospective review was conducted of spinal fusion cases for pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Various authors have also explored the application of TID rods for severe scoliosis treatment. Kwong et al [18] assessed patients who underwent posterior spinal fusion using a non-contoured titanium elastic nail on one side, performed in a single-stage surgery to achieve partial correction, while the contralateral side was instrumented, resulting in a 53.6% correction in the coronal plane. The authors suggested that temporary internal distraction in a single-stage setting could aid in gradually correcting severe pediatric spinal deformities during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various authors have also explored the application of TID rods for severe scoliosis treatment. Kwong et al [18] assessed patients who underwent posterior spinal fusion using a non-contoured titanium elastic nail on one side, performed in a single-stage surgery to achieve partial correction, while the contralateral side was instrumented, resulting in a 53.6% correction in the coronal plane. The authors suggested that temporary internal distraction in a single-stage setting could aid in gradually correcting severe pediatric spinal deformities during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that temporary internal distraction in a single-stage setting could aid in gradually correcting severe pediatric spinal deformities during surgery. Although common, neuromonitoring alerts are in fact reversible [18]. In a separate study involving 51 patients with severe scoliosis [19], temporary internal distraction rods were utilized in the surgical treatment, leading to an average Cobb reduction of up to 81%, surpassing that of Halo traction, and this improvement was maintained over long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation